Text Interpretation: Intention or Convention? - Gasparyan, Gayane (Armenian Folia Anglistika, 2010)
The article attempts to consider text interpretation process in the light of two phenomena that come to describe speech acts – intention and convention. Though both are of importance in terms of text interpretation, they take different positions in case of a national and non-national reader.